Advances in hydroscience. - Chow, Ven Te, 1919-1981 (Academic Press, 1967)
Advances in Hydroscience, Volume 4 covers selected topics encompassing several areas of special interest in hydroscience, including naval architecture, water waves, subsurface water, engineering hydraulics, and stochastic hydrology. This volume is composed of seven chapters, and begins with a summary of the basic principles and theories involved in hovering craft operating over water, which should be of interest to naval architects who may design such vehicles for special purposes. The succeeding chapters deal with the significance of soil moisture theory in the design of foundations and land.